For UHF Band Communication Systems Investigation of Multiple Frequency Exposure Effects - Zorlu, Elgin; Alagöz, İzzet; Elmas, Bahadır (Fırat University, 2022)
Electromagnetic radiation; It is a factor that shares our environment with us in our homes, workplaces, public transportation vehicles and crowded social events. This can be caused by base stations, mobile phones, wireless local area network devices or Radio-Television transmitters. In order to calculate the effects of electromagnetic radiation on the human body, it is necessary to know how much of this radiation is absorbed by the human body. For this reason, the Specific Absorption Rate of the sources that emit electromagnetic radiation should be calculated. In this study, in environments where people spent their time in everyday life, mobile phones, wireless modems from computers on the wireless local area network card and Bluetooth access that occurs on people who are exposed to electromagnetic radiation from electrical fields systems, single-user scenarios by simulations and crowded environments for scripted scenes and people that made the total electric field by calculating the value designated with the limits for safe exposure were compared with international standards. Using these electrical field values, the amount of electromagnetic radiation absorption in the human brain fluid and the temperature increases in the brain fluid during exposure were calculated and the results were reached.

Elektromanyetik radyasyon; evlerimizde, iş yerlerimizde, toplu taşıma araçlarında ve kalabalık sosyal etkinliklerde çevremizi bizimle paylaşan bir unsurdur. Bu durum baz istasyonlarından, mobil telefonlardan, kablosuz yerel alan ağ cihazlarından veya Radyo-Televizyon vericilerinden kaynaklanabilir. Elektromanyetik radyasyonun insan vücuduna olan etkilerini hesaplayabilmek için bu radyasyonun ne kadarının insan vücudu tarafından emildiğinin bilinmesi gereklidir. Bunun için de elektromanyetik radyasyon yayan kaynakların Özgül Emilim Oranı olarak bilinen değerleri hesaplanmalıdır. Bu çalışmada, insanların günlük yaşamda vakitlerini geçirdiği ortamlarda, cep telefonlarından, kablosuz modemlerden, bilgisayarların üzerindeki kablosuz yerel alan ağ erişim kartlarından ve Bluetooth sistemlerden kaynaklanan elektromanyetik radyasyona maruz kalan insanlar üzerinde oluşan elektriksel alanlar, tek kullanıcı ve kalabalık ortamlar için benzetimler yapılarak senaryolaştırılmış ve bu senaryolar gereği insanlar üzerindeki toplam elektriksel alan değeri hesaplanarak, uluslararası standartlar ile belirlenmiş emniyetli maruziyet sınırları ile karşılaştırılmıştır. Elde edilen bu elektriksel alan değerleri kullanılarak da insan beyin sıvısındaki elektromanyetik radyasyon soğurulma miktarları ile maruziyet süresince beyin sıvısında meydana gelen sıcaklık artışları hesaplanmış ve sonuçlara ulaşılmıştır.
UHF Bandı Haberleşme Sistemleri İçin Çoklu Frekans Maruziyeti Etkilerinin İncelenmesi
Keywords: Engineering; Mühendislik